PROCESS-TECHNOLOGY ORIENTED APPROACH FOR DEVELOPING MARKETING MODEL OF AN INDUSTRIAL GOOD - Зозульов, Олександр; Царьова, Тетяна; Гавриш, Юлія (SWorldJournal, 2025)
The article investigates the competitiveness of goods related with building product models according to structural, structural-dynamic and process approaches. In the article it is determined that widely used marketing models of product (model of three lev